The synergistic effect of hydroalcoholic extracts of Origanum vulgare, Hypericum perforatum and their active components carvacrol and hypericin against Staphylococcus aureus. (31st January 2019) - Bahmani, Mahmoud; Taherikalani, Morovat; Khaksarian, Mojtaba; Rafieian-Kopaei, Mahmoud; Ashrafi, Behnam; Nazer, Mohammadreza; Soroush, Setareh; Abbasi, Naser; Rashidipour, Marzieh
Aim: This study was designed to evaluate the synergistic activities of hydroalcoholic extracts of medicinal plants Origanum vulgare and Hypericum perforatum and their active components, carvacrol and hypericin against Staphylococcus aureus .Methods: The synergistic effects of the plants, as well as carvacrol and hypericin, were examined using a checkered method against S. aureus (ATCC 12600).Results: A fractional inhibitory concentration of 0.5 was obtained for combination of O. vulgare and H. perforatum and 0.49 for combination of the active ingredients carvacrol and hypericin, both of which indicated a synergistic effect.Conclusion: This preliminary evaluation demonstrated a synergistic property of O. vulgare and H. perforatum extracts in treating S. aureus infection. This study indicates that combination of the plants, as well as combination of carvacrol and hypericin, might be used as a new antibacterial strategy against S. aureus . Lay abstract: We studied and evaluated the synergistic activities of hydroalcoholic extracts of oregano and St John's wort and their active components, carvacrol and hypericin, against Staphylococcus aureus . The results suggest that a combination of oregano and St John's wort extracts, as well as a combination of hypericin and carvacrol, have potential for use as natural and effective combinations against S. aureus infections.